Pengaruh Media Pembelajaran Dalam Meningkatkan Hasil Belajar Akidah Akhlak Siswa Mi Al Azhar Tuban Badung - Ayu Laksmi; Novena Ade Fredyarini Soedjiwo; Rusmayani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research is motivated by the fact that the teaching and learning process of the subject of faith and morality (akidah akhlak) still relies predominantly on print media such as textbooks and largely employs lecture-based teaching methods. The objectives of this research are as follows: 1) To determine the difference in learning outcomes in faith and morality between students using video learning media and those using print media; 2) To assess the extent of the contribution of video learning media to the improvement of learning outcomes in faith and morality among students who study using print media. This research follows a quantitative approach, specifically a quasiexperimental design known as Nonequivalent Control Group Design. The results of the study indicate that: 1) There is a difference in learning outcomes in faith and morality between students in the experimental and control groups, with tvalue = 2.249 > ttable = 1.677 at a significance level of 0.05. 2) The contribution of the learning model to students' learning outcomes in faith and morality is 54%, while the remaining 46% is influenced by other factors not included in this study.